PENGARUH PENCATATAN PERNIKAHAN BERBASIS SIMKAH WEBSITE DI KUA KECAMATAN DELANGGU - Rahmanda, Safira (LPPM STAI Muhammadiyah Probolinggo, 2025)
Since 2007, the Directorate General of Islamic Community Guidance has been trying to improve the quality of services of the Religious Affairs Office (KUA) through the application of information technology, in line with the times. One of the modernization steps taken is to implement the Marriage Management Information System (SIMKAH) application which is integrated with e-marriage at the Sub-district KUA, replacing the manual system previously used. The main objective of SIMKAH is to improve the efficiency and quality of marriage administration at the Sub-district KUA. SIMKAH is a special application used for marriage registration at all KUAs in Indonesia, which utilizes internet facilities to ensure a more accurate, fast, and secure marriage registration process. This study aims to examine the direct impact of the implementation of SIMKAH as a modern marriage registration administration system in the field. Using empirical methods, this study focuses on identifying the effects of changes in the marriage registration administration system at the Delanggu Sub-district KUA, using a purposive sampling technique. The results of the study indicate that although the SIMKAH application has been implemented well at the Delanggu Sub-district KUA, there are still challenges in the understanding and use of the application by the community. However, the use of this application also supports the implementation of laws and regulations regarding the minimum age limit for marriage. Keywords: SIMKAH; Marriage Registration; Implications